2021
DOI: 10.1371/journal.pbio.3001431
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal HSF-1 coordinates the propagation of fat desaturation across tissues to enable adaptation to high temperatures in C. elegans

Abstract: To survive elevated temperatures, ectotherms adjust the fluidity of membranes by fine-tuning lipid desaturation levels in a process previously described to be cell autonomous. We have discovered that, in Caenorhabditis elegans, neuronal heat shock factor 1 (HSF-1), the conserved master regulator of the heat shock response (HSR), causes extensive fat remodeling in peripheral tissues. These changes include a decrease in fat desaturase and acid lipase expression in the intestine and a global shift in the saturati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
25
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(29 citation statements)
references
References 78 publications
(99 reference statements)
4
25
0
Order By: Relevance
“…Pioneering work by Lee and Kenyon showed that a reduction in HSF-1 function further shortened lifespan at 22.5°C. Consistent with this, recent data show that overexpression of hsf-1 in neurons protects animals at 25°C and extends their lifespan ( Chauve et al, 2021 ). Overexpression of the proteasomal subunit rpn-6.1 extends lifespan independently of HSF-1 in a DAF-16-dependent manner at 25°C ( Vilchez et al, 2012 ).…”
Section: Modulation Of Organismal Longevity By Temperaturesupporting
confidence: 64%
“…Pioneering work by Lee and Kenyon showed that a reduction in HSF-1 function further shortened lifespan at 22.5°C. Consistent with this, recent data show that overexpression of hsf-1 in neurons protects animals at 25°C and extends their lifespan ( Chauve et al, 2021 ). Overexpression of the proteasomal subunit rpn-6.1 extends lifespan independently of HSF-1 in a DAF-16-dependent manner at 25°C ( Vilchez et al, 2012 ).…”
Section: Modulation Of Organismal Longevity By Temperaturesupporting
confidence: 64%
“…For qPCR reactions, cDNA (~1200 ng/μl) was diluted fivefold and prepared for amplification using a BioRad SYBR Green Supermix Kit with the primers for nucleoporin genes listed in key resource table as well as pmp-3 primers from Chauve et al, 2021 . For each biological replicate (two wild type and two ndc1Δ ), four technical replicates were performed.…”
Section: Methodsmentioning
confidence: 99%
“…Hsf-1 is an important long-lived transcription factor that acts downstream of the IIS and is widely studied. It has been reported that downregulation of the IIS pathway, along with coactivation of Hsf-1, is necessary for the prolongation of life ( Chauve et al, 2021 ). To investigate whether Hsf-1 is required for SVHRSP-mediated life extension, we tested the effects of 20- and 40-μM SVHRSP on Hsf-1 (SY441) mutant worms PS3551.…”
Section: Resultsmentioning
confidence: 99%